Teaching Interfaith Relations at Universities in the Arab Middle East: Challenges and Strategies - Josef Meri (19560256) (2021)
This study explores the present state of teaching Interfaith/Interreligious Relations at universities in the Arab Middle East. First, it considers the definition and various approaches to teaching Interfaith Relations by leading proponents of Interreligious Studies in the West such as Oddbjørn Leirvik and Marianne Moyaert within a theoretical framework that is sensitive to the Arab Middle Eastern context. It explores several key factors in Arab society that have prevented the teaching of Interfaith Relations in universities. The discussion then turns to the unique Dar Al-Kalima University (Palestine) Interreligious Dialogue Inter-Regional Curriculum initiative and its significance for teaching Interfaith Relations in the university. Finally, the study examines the case study method of teaching developed by Diana Eck at Harvard University, which can be adapted to a Middle Eastern context and offers two unique case studies for university teachers. Other Information Published in: Religions License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/rel12050330